THE FISHERY AND BIOLOGY OF CRABS OF KAKINADA REGION - Devi, S Lalitha (Indian Journal of Fisheries, 2011)
Kakinada area has a lucrative crab fishery throughout the year with peak landings during March to May and August to November. The morphometric relationships, age and growth, size at maturity, breeding season and sex ratio in PorUtmis pelagicus, P. sangiiinolentiis and Scylla serrata are reported. The relation of fecundity to carapace length in P. sanguinolentiis is discussed. An incidence of infection in Charybdis cnwicUa by a rhizocephalan was noticed. Jn P. sanguinolentiis 21% of the eggs were infested by parasitic copepods